LIBRARY AUTOMATION SYSTEM OF ACADEMIC LIBRARIES: A MULTICULTURAL PARADIGM - Benhur Abdulaup Asid (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This research was conceived to create a picture of the Library Automation System of Academic Libraries in Zamboanga City. The study was premised on null hypotheses which were tested at 0.05 level of significance. The quantitative research design employing descriptive survey method was used. In the selection of respondents, the systematic random sampling was also employed and the five (5) point likert-type questionnaire-checklist was utilized. The findings revealed that the extent of library automation system in terms of: Administration and Staffing: Facilities, and Services of the (3) three Higher Education Institutions (HEls) involved was found that it is moderately implemented. However, HEIs from public institution showed undesirable results in some areas compared to HEIs from private institution, where the library automation system has been helpful in facilitating loaning services in a multicultural level of clientele. The significant differences among institutions do exist in the library services offered showing that the respondents have their own library services needed to satisfy their needs. It also shows that Academic Libraries are for technological advancement using different library automation systems for different reasons to facilitate library transactions. However, the posited null hypothesis is accepted where all average responses are from 3.40 to 4.19 criteria, implying that whatever ethnic profile respondents belong (multicultural clientele), their responses were similar and were rated within the satisfactory criteria. Therefore, multicultural clientele is not a factor of having poor utilization in the transformation of library services using the Library Automation System. Based on the findings, the full implementation of the library automation system, upgrading of library technology tools and e-resources, creating a functional and interactive library web page, and designing innovative library programs using social media tools to support the educational system with diverse clientele were recommended.